Energy-Based Control Technique for Monoinverter Dual Parallel PMSM With Different Parameters - Boroujeni, Mojtaba Mansouri; Markadeh, Gholamreza Arab (IEEE transactions on industrial electronics (1982), 2022)
This article declares two control strategies, named " average-model based " (AMB) and " energy-based " (EB) control methods, to control a monoinverter dual parallel surface-mounted permanent magnet synchronous motor (MIDP-PMSM) with different parameters. Up to now, it has been assumed that two parallel PMSMs have the same parameters, so the controller has been designed based on this simplifier assumption. To extend the control subject to MIDP-PMSMs with different parameters, two new methods are proposed and compared in this article. The average value of both motors' parameters is used in the AMB control design, while in the proposed EB control method, each motor's parameters separately contribute to designing the control laws. The proposed methods are based on the " mean-difference " technique. These methods have been compared by mathematical analysis regarding the torque per total ampere ratio, the copper losses and the dynamic response of motors' speed. The MATLAB simulation and experimental implementation have been carried out to verify the proposed methods. The results have shown that the EB control method has better performance than the other.